2015
DOI: 10.1097/mlr.0000000000000323
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Provider Designation and Female-specific Cancer Screening in Women Veterans

Abstract: Background In 2010, the Department of Veterans Affairs Healthcare System (VA) implemented policy to provide Comprehensive Primary Care (for acute, chronic, and female-specific care) from designated Women’s Health providers (DWHPs) at all VA sites. However, since that time no comparisons of quality measures have been available to assess the level of care for women Veterans assigned to these providers. Objectives To evaluate the associations between cervical and breast cancer screening rates among age-appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…We also caution that satisfaction scores, while important measures of patient care, are not objective measures of quality or costs. It has been separately reported that patients seen by DWHPs report higher rates of certain quality measures of women’s health care, that is, indicators regarding mammography and cervical cancer screening (Bean-Mayberry et al, 2015). Like this study, the latter study focused on women only.…”
Section: Discussionmentioning
confidence: 99%
“…We also caution that satisfaction scores, while important measures of patient care, are not objective measures of quality or costs. It has been separately reported that patients seen by DWHPs report higher rates of certain quality measures of women’s health care, that is, indicators regarding mammography and cervical cancer screening (Bean-Mayberry et al, 2015). Like this study, the latter study focused on women only.…”
Section: Discussionmentioning
confidence: 99%
“…In a national sample of women Veterans aged 21 to 64 years, who were assigned VA PCPs in Fiscal Year 2012, 93% received cervical cancer screening over a 3-year interval. 39 In this same study, 87% of women aged 50 to 69 had received a mammogram over a 2-year interval. These high rates in screening have been achieved, in large part, due to VA investing in performance measurement, informatics support for decision support and panel management, and organizational change initiatives.…”
Section: Prevention and Screeningmentioning
confidence: 92%
“…Women Veterans assigned to WH-PCPs are more likely, compared with those assigned to VA PCPs who are not WH-PCPs, to have received needed breast and cervical cancer screening. 39 It is unknown the extent to which this observed difference is due to differences in PCP knowledge regarding screening guidelines or use of provider or clinic-based systems for coordinating and supporting screening.…”
Section: Prevention and Screeningmentioning
confidence: 99%
“…Despite these challenges, WH-PCPs are of benefit to women Veterans. Those who are cared for by WH-PCPs receive better preventative care 20 and have higher patient satisfaction 21 than women Veterans cared for by PCPs without the WH designation (referred to hereafter as general PCPs). Similar patterns hold for women patients inside and outside the VHA who receive care in women's health clinics [22][23][24] compared to general primary care clinics.…”
Section: Introductionmentioning
confidence: 99%